Sea Level Rise in the Samoan Islands Escalated by Viscoelastic Relaxation After the 2009 Samoa‐Tonga Earthquake. Issue 4 (15th April 2019) - Han, Shin‐Chan; Sauber, Jeanne; Pollitz, Fred; Ray, Richard
Abstract: The Samoan islands are an archipelago hosting a quarter million people mostly residing in three major islands, Savai'i and Upolu (Samoa), and Tutuila (American Samoa). The islands have experienced sea level rise by 2–3 mm/year during the last half century. The rate, however, has dramatically increased following the M w 8.1 Samoa‐Tonga earthquake doublet (megathrust + normal faulting) in September 2009. Since the earthquake, we found large‐scale gravity increase (0.5 μGal/year) around the islands and ongoing subsidence (8–16 mm/year) of the islands from our analysis of Gravity Recovery And Climate Experiment gravity and GPS displacement data. The postseismic horizontal displacement is faster in Samoa, while the postseismic subsidence rate is considerably larger in American Samoa. The analysis of local tide gauge records and satellite altimeter data also identified that the relative sea level rise becomes faster by 7–9 mm/year in American Samoa than Samoa. A simple viscoelastic model with a Maxwell viscosity of 2–3×10 18  Pa s for the asthenosphere explained postseismic deformation at nearby GPS sites as well as Gravity Recovery And Climate Experiment gravity change. It is found that the constructive interference of viscoelastic relaxation from both megathrust and normal faulting has intensified the postseismic subsidence at American Samoa, causing ~5 times faster sea level rise than the global average. Our model indicates that this trend is likely to continue for decades and result in sea level rise of 30–40 cm, which is independent of and in addition to anticipated climate‐related sea level rise. It will worsen coastal flooding on the islands leading to regular nuisance flooding. Key Points: After the 2009 earthquake, Samoa islands entered a new era of exacerbated (3‐6 times faster) sea level rise due to ongoing land subsidence Constructive interference of viscoelastic relaxation from megathrust and normal faulting intensified the postseismic subsidence A viscoelastic relaxation model, constrained by GRACE and GPS data, is used to unravel the observed relative sea level changes